CEO duality and firm performance : a case study of Tenaga Nasional Bhd, Telekom Malaysia Bhd and YTL Power International Bhd. / Hilwani Hariri, Norshimah Abdul Rahman and Noraini Abd Rahim - Hariri, Hilwani; Abdul Rahman, Norshimah; Abd Rahim, Noraini (Unit of Research, Development and Commercialization (URDC),UiTM Perlis, 2004)
There have been many researches on the impact of CEO duality on firm performance done in the UK and USA. Where Malaysian companies are concerned, there have been limited studies. The purpose of this paper is to review the literature on the topic and to compare their findings with three Malaysian companies. Previous research findings have been varied as some found that duality enhanced the firms' performance, while others did not find significant difference in performance among firms adopting duality and separate structure. This study used the data of three listed companies, two of which have similar background, being monopolies in their industries and government owned, regulated, supported and protected, while the other company is owned by individuals, successful and a leader in its industry. Our findings showed that Tenaga Nasional Berhad perform better after it changed to separate board structure, while YTL performed well under duality.